Testosterone suppression plus enzalutamide versus testosterone suppression plus standard antiandrogen therapy for metastatic hormone-sensitive prostate cancer (ENZAMET): an international, open-label, randomised, phase 3 trial. Issue 4 (April 2023) - Sweeney, Christopher J; Martin, Andrew J; Stockler, Martin R; Begbie, Stephen; Cheung, Leanna; Chi, Kim N; Chowdhury, Simon; Frydenberg, Mark; Horvath, Lisa G; Joshua, Anthony M; Lawrence, Nicola J; Marx, Gavin; et al.
Summary: Background: The interim analysis of the ENZAMET trial of testosterone suppression plus either enzalutamide or standard nonsteroidal antiandrogen therapy showed an early overall survival benefit with enzalutamide. Here, we report the planned primary overall survival analysis, with the aim of defining the benefit of enzalutamide treatment in different prognostic subgroups (synchronous and metachronous high-volume or low-volume disease) and in those who received concurrent docetaxel. Methods: ENZAMET is an international, open-label, randomised, phase 3 trial conducted at 83 sites (including clinics, hospitals, and university centres) in Australia, Canada, Ireland, New Zealand, the UK, and the USA. Eligible participants were males aged 18 years or older with metastatic, hormone-sensitive prostate adenocarcinoma evident on CT or bone scanning with 99 m Tc and an Eastern Cooperative Oncology Group performance status score of 0–2. Participants were randomly assigned (1:1), using a centralised web-based system and stratified by volume of disease, planned use of concurrent docetaxel and bone antiresorptive therapy, comorbidities, and study site, to receive testosterone suppression plus oral enzalutamide (160 mg once per day) or a weaker standard oral non-steroidal antiandrogen (bicalutamide, nilutamide, or flutamide; control group) until clinical disease progression or prohibitive toxicity. Testosterone suppression was allowed up to 12 weeks before randomisation and for up to 24 months as adjuvant therapy. Concurrent docetaxel (75 mg/m 2 intravenously) was allowed for up to six cycles once every 3 weeks, at the discretion of participants and physicians. The primary endpoint was overall survival in the intention-to-treat population. This planned analysis was triggered by reaching 470 deaths. This study is registered with ClinicalTrials.gov, NCT02446405, ANZCTR, ACTRN12614000110684, and EudraCT, 2014-003190-42. Findings: Between March 31, 2014, and March 24, 2017, 1125 participants were randomly assigned to receive non-steroidal antiandrogen (n=562; control group) or enzalutamide (n=563). The median age was 69 years (IQR 63–74). This analysis was triggered on Jan 19, 2022, and an updated survival status identified a total of 476 (42%) deaths. After a median follow-up of 68 months (IQR 67–69), the median overall survival was not reached (hazard ratio 0·70 [95% CI 0·58–0·84]; p<0·0001), with 5-year overall survival of 57% (0·53–0·61) in the control group and 67% (0·63–0·70) in the enzalutamide group. Overall survival benefits with enzalutamide were consistent across predefined prognostic subgroups and planned use of concurrent docetaxel. The most common grade 3–4 adverse events were febrile neutropenia associated with docetaxel use (33 [6%] of 558 in the control group vs 37 [6%] of 563 in the enzalutamide group), fatigue (four [1%] vs 33 [6%]), and hypertension (31 [6%] vs 59 [10%]). The incidence of grade 1–3 memory impairment was 25 (4%) versus 75 (13%). No deaths were attributed to study treatment. Interpretation: The addition of enzalutamide to standard of care showed sustained improvement in overall survival for patients with metastatic hormone-sensitive prostate cancer and should be considered as a treatment option for eligible patients. Funding: Astellas Pharma.